2003
DOI: 10.1001/archotol.129.9.944
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Salivary Gland Neoplasms With Fast Neutron Radiotherapy

Abstract: Neuron radiotherapy is an effective treatment for patients with salivary gland neoplasms who have gross residual disease and achieves excellent local-regional control in patients without evidence of gross disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 25 publications
7
98
1
4
Order By: Relevance
“…Huber found in his comparison of neutron therapy versus mixed beam versus photon therapy that although the complication rates were higher with neutron therapy, 5 of 27 (17%) versus 2 of 21 (10%) versus 1 of 25(4%) respectively, this was not significant [19]. Douglas had a 6 year actuarial Grade 3 and 4 toxicity of 10% [17]. There was no significant difference in complication rates between the different dose and fractionation groups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Huber found in his comparison of neutron therapy versus mixed beam versus photon therapy that although the complication rates were higher with neutron therapy, 5 of 27 (17%) versus 2 of 21 (10%) versus 1 of 25(4%) respectively, this was not significant [19]. Douglas had a 6 year actuarial Grade 3 and 4 toxicity of 10% [17]. There was no significant difference in complication rates between the different dose and fractionation groups.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent results from Seattle have shown a 59% LRC rate and 67% cause specific survival (CSS) at 6 years [17] and 76.5% LC and 68.2% CSS at 7 years in major salivary gland tumours, the majority of which had macroscopically resected disease [18]. Huber has shown a 75% 5-year LCR rate for advanced adenoid cystic carcinomas [19].…”
Section: Discussionmentioning
confidence: 99%
“…LC was also significantly improved by the application of high-precision techniques, dose-escalation and high linear energy transfer radiation [7,[33][34][35][36]. Both IMRT and FSRT provide better LC than conventional radiotherapy techniques, achieving 3-year progression-free survival (PFS) rates of 38% [37].…”
Section: Malignant Salivary Gland Tumours: Adenoid Cystic Carcinomamentioning
confidence: 99%
“…Both IMRT and FSRT provide better LC than conventional radiotherapy techniques, achieving 3-year progression-free survival (PFS) rates of 38% [37]. The highest LC rates achieved to date, at 75-100% [35,36], were achieved by neutron radiation, albeit at the cost of significant late toxicity.…”
Section: Malignant Salivary Gland Tumours: Adenoid Cystic Carcinomamentioning
confidence: 99%
“…In a series of 102 patients 80 treated to a median dose of 71.6 Gy with protons, the 5-year local control was 86% (median followup-6.6 years), with very low rates of ocular toxicity. The largest study 81 of fast-neutrons in salivary gland cancers reported a 6-loco-regional control and cause-specific survival of 59% and 67% respectively, with a 10% incidence of grade 3-4 late toxicity at a median follow-up of 36 months establishing the efficacy of such therapy.…”
Section: Particle-beam Therapymentioning
confidence: 99%